Community-Based Social Capital: The Key to Inclusive Political Initiatives from Gender Equality, Disability, And Social Inclusion (GEDSI) Perspective - Elly Malihah; Siti Nurbayani; Siti Komariah; Lingga Utami; Rengga Akbar Munggaran; Arindini Ayu Kisvi Rizkia; Andreian Yusup; Faiq Akmal Fadhillah; Rexa Putra Pratama (Jurnal Pendidikan Ilmu Sosial, 2023)
This research aims to develop social capital through a political education model that involves urban female cadre communities in increasing political involvement based on Gender Equality, Disability, and Social Inclusion (GEDSI). The research method employs a qualitative approach. This research involved 2 informants responsible for implementing political education regulations and 4 urban female cadre informants. Data collection methods include in-depth interviews and focus group discussions, which are subsequently analyzed through coding. The findings reveal that GEDSI-based women's political education serves as a benchmark for increasing the social capital of women’s mobilization partners, enabling them to acquire the abilities, skills, and political acumen necessary to boost confidence and empower women in formulating policies addressing the needs, challenges, and solutions for their communities. This research contributes by emphasizing that GEDSI-based political education for women encourages the development of political competence among female mobilization cadre partners advocating for gender justice, accessibility for people with disabilities, and the welfare of marginalized groups.